Selection and Prioritization of Test Cases by using Bees Colony - Shahbaa Khaleel; Ragad khaled (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research, the bees swarm intelligence was studied to appointment it to serve software engineering. And that was performed through using Artificial Bees Colony ABC Algorithm in selection of test cases for the software written by C++ language in an automatic way since to enable the corporation which develops the software to save time, effort  and costs that required for testing phase and regression testing activity, which is always evaluated by 50% of the product cost. The proposed work can reduce test cases that are used in the tests of software and in regression testing activity ,also will make prioritization to the test cases, that are produced by the best selection process, by using Greedy Algorithm and Genetic Algorithm. the proposed work was applied practically on some programs – that differ in number of lines of code-.the result that appeared reduce number of test cases and make test cases in certain ordering that assists testing and regression testing for the software in safe mode and short time .